Traços funcionais do zooplâncton (copépodos) determinam duração da facilitação na dominância de cianobactérias filamentosas - Oliveira Júnior, Ewaldo Leitão de (2018)
Top-down regulations in trophic chain depend on herbivore grazing traits and producers edibility. By actively selecting nutritious eukaryotic phytoplankton and rejecting toxic cyanobacteria, grazing copepods may contribute to cyanobacteria blooms and dynamics. In tropical environments, for instance, copepods commonly cooccur with cyanobacteria blooms, raising the question whether they can facilitate cyanobacteria dominance. We experimentally tested the effects of two groups of copepods with different feeding modes – calanoid Notodiaptomus iheringi (active filter feeding) and cyclopoid Thermocyclops decipiens (ambush feeder) – on the competition of an eukaryotic phytoplankton Cryptomonas and the filamentous cyanobacteria Cylindrospermopsis raciborskii. We assessed grazing in 1L batch cultures for seven days, starting with 10-fold initial dominance of Cryptomonas. Copepods demonstrated initial rejection of Cylindrospermopsis filaments, but while cyclopoids slightly increased grazing on cyanobacteria in extended experimental periods, calanoids reversed to clear more particles of cyanobacteria. Despite differences on grazing, both zooplankton decreased cyanobacteria filaments size similarly, reducing it in ~70%. We also performed experiments testing competition between phytoplankton that showed no interference on each other growth rates, assuring that results from grazing experiment are addressed to zooplankton feeding. Here, we demonstrated that copepod selectively avoidance of filamentous cyanobacteria Cylindrospermopsis may facilitate its dominance, depending on time and alternative food concentration. Cyclopoid, rather than calanoid, grazing may be an appropriate mechanism to explain filamentous cyanobacteria dominance, as they had lower impact on cyanobacteria abundance. This mechanistic approach understanding trophic dynamics using traits of different groups (i.e. copepods and cyanobacteria) is especially relevant in light of the more intense warmer and eutrophic world that will promote cyanobacteria bloom, and increase complexity of such interactions.